Digital Capability, Promotion Strategy and AR-Based Social Media for Indonesian Businesswomen in West Java - Suryawardani, Bethani; Marcelino, Dandy; Wulandari, Astri; Prawita, Fat’hah Noor (Jurnal Penyuluhan, 2025)
IWAPI West Java is a center for community collaboration which has an impact on increasing the creativity of residents, therefore the various programs it implements need support from all levels of society. Functionally, IWAPI activation is expected to be a means of locating the activities of women entrepreneurs in West Java Province as well as a means of providing and increasing access and mastery of technology for its users. Their role is also very potential for development in the Creative Economy sector, so these creative economy actors need to be continuously nurtured and empowered in a sustainable manner so that they can develop and progress further, considering that the female business actors who are members of IWAPI West Java still have very little knowledge, especially regarding with digital marketing and business management. Based on the description of target partner problems that has been described in the previous sub-chapter, the solutions offered by our team can be categorized into two aspects, namely the technology side and the management side regarding business management aspects and digital marketing tools which can be described as follows. First, providing workshops and assistance regarding how to manage a business effectively by implementing an integrated financial and operational management and integration system. Second, develop and implement a digital promotion strategy to promote and improve organizational operational optimization. Digital tools will be developed through providing workshops on social media marketing and other promotion tools. Third, providing a workshop on Augmented Reality Based Social Media Content. It is hoped that by creating interesting information and promotional content on social media using AR technology, the promotions created will be able to attract the attention and interest of potential consumers.